Deep vein thrombosis: experience from a tertiary care centre in central India - Khandait, Vinod; Khandait, Harshwardhan; Ali, Shadman (International Journal of Research in Medical Sciences, 2019)
Background: Deep vein thrombosis is a disease of potentially serious consequences and is still often unsuspected. The present study was undertaken to look into etiological factors, management approaches and complications in patients presenting primarily with DVT at a tertiary care centre. Methods: This was a descriptive study profiling 75 confirmed DVT cases admitted at a tertiary care government hospital over two years. Detailed assessment included thorough clinical examination, duplex venous ultrasound and basic investigations, along with special investigations and CT angiography in selected few. Appropriate management was provided, and details recorded. Patients were followed up clinically and by ultrasound after 1 week, 2 weeks and 3 months. The complications, if any were also recorded. Results: The mean age of participants was 39.5±14.4 years, with 28% between 30-39 years. Majority (40%) did not have any obvious predisposing factor and most of them presented with pain and swelling. Most (52%) of the cases had involvement of both proximal and distal veins, 45.33% cases had involvement of only proximal veins whereas only 2.67% had restricted involvement of distal veins. Around 60% of cases have complete clinical resolution and approximately 50% cases have complete ultrasonographic resolution at the end of 3 months. Conclusions: Young adults without any obvious risk factors may develop and present with DVT and hence factors leading to thrombosis in them are recommended to be thoroughly evaluated. Duplex venous ultrasound is reliable non-invasive diagnostic modality and is recommended for diagnosis of DVT in clinically suspected cases.